MODELING AND ANALYSIS OF THE "AIRPLANE-AUTOPILOT" SYSTEM IN DESCENDING ATMOSPHERIC DISTURBANCE: MODELING AND ANALYSIS OF THE "AIRPLANE-AUTOPILOT" SYSTEM IN DESCENDING ATMOSPHERIC DISTURBANCE - Getsov, Petar; Jordanov, Dimitar; Bo, Wang; Getsov, St. (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The study examined the behavior of the "autopilot-airplane" system under a strong downward impulse. The airplane is modeled through a complex turbulent turbulence that forms at mountain peaks. The airplane’s behavior is controlled and controlled by various autopilots. Comments and conclusions were made on the results of modeling for a possible catastrophic situation if the stock height is less than 50 m and the control is from a simple pilot structure.